Information value of patent litigation and industry competition in Taiwan - Lee, Jun-De; Wang, Yi-Hsien; Lin, Ching-Wen; Lin, Hsin-Ham (Technological and Economic Development of Economy, 2013)
Internationally, news on patent infringement is often seen, and patent infringement law-suits affect stock prices. However, fewer studies have discussed how market reflects corporate value and impact of patent infringement lawsuit on investment returns when a patent infringement lawsuit occurs and the news is released. This study applied event study to discuss changes in information value of plaintiffs and defendants, and information value difference of different patent lawsuit sources in competitive environment. The empirical results showed that patent infringement lawsuits may cause negative perception of investors or insider shareholders. This event may become an arbitrage opportunity. Through five forces analysis, the lawsuits from various sources are bad news. Reverse correction is conducted after the event, and makes stock price rational. Thus, in Taiwan market, patent infringement lawsuit is negative news for plaintiff and defendant.